Neutralizing activities against seasonal influenza viruses in human intravenous immunoglobulin - Onodera H (Dove Medical Press, 2017)
Hiroyuki Onodera,1 Takeru Urayama,2 Kazue Hirota,3 Kazuhiro Maeda,3 Ritsuko Kubota-Koketsu,3,4 Kazuo Takahashi,5 Katsuro Hagiwara,6 Yoshinobu Okuno,3 Kazuyoshi Ikuta,3,4 Mikihiro Yunoki,2,4,6 1Medical Information Department, 2Research and Development Division, Japan Blood Products Organization, Tokyo, 3Research and Development Division, The Research Foundation for Microbial Diseases of Osaka University, Kagawa, 4Former Department of Virology, Research Institute for Microbial Diseases, Osaka University, 5Virology Division, Department of Infectious Diseases, Osaka Prefectural Institute of Public Health, Osaka, 6Pathogenic Risk Evaluation, Graduate School of Veterinary Medicine, Rakuno Gakuen University, Hokkaido, Japan Abstract: Influenza viruses A/H1N1, A/H3N2, and B are known seasonal viruses that undergo annual mutation. Intravenous immunoglobulin (IVIG) contains anti-seasonal influenza virus globulins. Although the virus-neutralizing (VN) titer is an indicator of protective antibodies, changes in this titer over extended time periods have yet to be examined. In this study, variations in hemagglutination inhibition (HI) and VN titers against seasonal influenza viruses in IVIG lots over extended time periods were examined. In addition, the importance of monitoring the reactivity of IVIG against seasonal influenza viruses with varying antigenicity was evaluated. A/H1N1, A/H3N2, and B influenza virus strains and IVIG lots manufactured from 1999 to 2014 were examined. The HI titer was measured by standard methods. The VN titer was measured using a micro-focus method. IVIG exhibited significant HI and VN titers against all investigated strains. Our results suggest that the donor population maintains both specific and cross-reactive antibodies against seasonal influenza viruses, except in cases of pandemic viruses, despite major antigen changes. The titers against seasonal influenza vaccine strains, including past strains, were stable over short time periods but increased slowly over time. Keywords: IVIG, influenza, seasonal, neutralization, vaccine